STAKEHOLDERS' EXPECTATIONS TOWARD THE TEACHING OF ENGLISH AT TOURS AND TRAVEL STUDY PROGRAM: a case study at one secondary vocational school in bogor - Herawati, Atti (2006)
This study aimed to investigate stakeholders' expectations towards the teaching of English at Tours and Travel study program. The stakeholders in this study are the students, the teachers, and the supervisor; while the expectations are the materials and the teaching methods needed. There are three questions that led the study: 1) What are stakeholders' expectations towards the teaching of English? 2) How is the relevance of the content of the textbook with stakeholders' expectations?; and 3) How do teachers enhance the materials in the textbook to meet stakeholders' expectations? The study employed a case study with qualitative approach. Questionnaire, interview, and documentary were used to collect data. The three instruments were used to triangulate the data and to check the validity of the data given by each group of stakeholder. From the data analysis, it was found that the stakeholders expected the materials and the teaching methods which focus on communicative competence and language skills development. It was also found that stakeholders' expectations were not relevant with the choice of the textbook because the contents of the textbook are not communicative and are not fully relevant with the curriculum. It is suggested accordingly, that instead of using published textbooks, the teachers develop materials based on the students' needs.